Literature review: Philosophical Views on Ecotourism-Based Contextual Science Learning - Hamidi Hamidi; Muhammad Sarjan; Sudirman Sudirman; Agus Muliadi; Iswari Fauzi; Muhammad Yamin; Asrorul Azizi; Muh. Zaini Hasanul Muttaqin; Mulia Rasyidi; Bakhtiar Ardiansyah; Yusran Khery; Rindu Rahmatiah (Pascasarjana, Mataram University, 2022)
Ecotourism-based contextual science learning is one of the sciences about learning in the science field which is carried out with a contextual approach (CTL) and then associated with its meaning in the field of ecotourism. Science is studied in 3 (three) major aspects of philosophy, namely ontology, epistemology, and axiology. Ecotourism-based contextual science learning, ontologically, the discussion focuses on ecotourism-based contextual science learning. Does learning really exist? Or is it just a name? How is it different from other learning? So contextual science learning based on ecotourism ontologically tries to prove and examine that science can really be proven to exist. The epistemology of ecotourism-based contextual science learning basically talks about the basics, sources, characteristics, truths, and ways to gain knowledge about ecotourism-based contextual science learning. The most important aspects discussed in the epistemology of ecotourism-based contextual science learning are the sources and methods of that knowledge. So, when ecotourism-based contextual science learning is highlighted through epistemology, the discussion is focused on how the sources are used in developing the knowledge and what methods are used because each type of knowledge has different sources and methods of knowledge. When ecotourism-based contextual science learning was born, he actually had to or had carried out an axiological test